Ragamuffin kid the boy without a smile : a story based on Juan Luna's painting Ragamuffin - Chong, Grace Dacanay (Stories in art, 2004)
Ragamuffin kid is a story of a lost boy named Bulan yearning for a love that is often taken for granted--love from one's own family.